Pengaruh Project Based Learning dengan Media Digital Microsite terhadap Keterampilan Berpikir Kritis Siswa Kelas VII Pada Klasifikasi Makhluk Hidup - Thamaradiva, Giska Efriandevi; Rambitan, Vandalita M.M.; Tindangen, Makrina; Lumowa, Sonja V.T. (PendIPA Journal of Science Education, 2025)
This study aimed to determine the effect of the project based learning model with digital microsite media on the critical thinking skills of class VII students at SMP Negeri 1 Samarinda. This study used a quasi-experimental design method with a non-equivalent control group design. The sample consisted of 20 students, with the experimental class using the project based learning model and the control class using the conventional model. The results showed that in the experimental class, the average pre-test and post-test scores increased from 60.35 to 86.95 with an N-Gain of 0.67. While in the control class, the average pre-test and post-test scores increased from 59.7 to 71.65 with an N-Gain of 0.29. The T-test results show that the significance value is 0.000 <0.0005 with t count> t table, so it can be concluded that the project based learning model with digital microsite media has a significant effect on the critical thinking skills of class VII students of SMP Negeri 1 Samarinda on the material of classification of living things.